Hair regrowth in alopecia areata and re‐pigmentation in vitiligo in response to treatment: Commonalities and differences - Yamaguchi, Hiroki L.; Yamaguchi, Yuji; Peeva, Elena (Journal of the European Academy of Dermatology and Venereology, 2025)
Both alopecia areata (AA) and vitiligo share common pathogenesis involving, interferon‐γ (IFN‐γ) and interleukin‐15 (IL‐15) signalling pathways that activate cytotoxic CD8+ T lymphocytes. These shared mechanisms may explain why both diseases respond to currently available treatments (e.g. topical/systemic corticosteroid) and emerging treatment modalities. As compared with the speed of re‐pigmentation in vitiligo lesions, the regeneration of pigmented terminal hair follicles in AA lesions appears fast in response to treatments targeting the inhibition of the Janus kinases (JAKs) and other kinases. We summarize the commonalities and differences between AA and vitiligo focusing on the treatment modalities, followed by recent findings associated with hair follicle stem cells (HFSC) in hair bulge (HBg) and melanocyte stem cells (McSC) in HBg and hair germ (HGm). We then discuss how HFSC and HGm‐McSC are involved in the initiation of anagen phase, followed by pigmented terminal hair regrowth in the recovering AA lesions in association with immunology. We also discuss how HBg‐McSC contribute to the migration of fully dendritic mature melanocytes into interfollicular epidermis and the equal distribution of melanin in recovering vitiligo lesions. Finally, we present four hypotheses to elucidate the delayed distribution of melanin by mature melanocytes in depigmented vitiligo lesions from the aspects of stem cell biology, as compared with quick hair recovery in AA: (1) McSC are less abundant than HFSC. (2) McSC require a long travel, whereas HFSC reside close to hair regeneration trigger point. (3) Keratinocyte scaffold to accept melanin is not well preserved, whereas scaffold for hair regrowth is well preserved. (4) Inhibitors targeting JAKs and other kinases have less direct effects on melanocyte proliferation and differentiation in vitiligo than hair regrowth in AA. Our review provides an overview of treatment modalities and bridges the gap between scientific advancement and clinical practice in AA and vitiligo management. Hair Regrowth in Alopecia Areata. This scheme summarizes recent findings in hair follicle stem cell biology and their implication to regrow hair in alopecia areata. Hair follicle stem cells reside in hair bulge abundantly. Anagen drivers are enhanced and suppressed expression levels of activators and repressors at telogen, respectively. Noradrenaline secreted from niche activates hair follicle regeneration via ADRB2, FOXP1 and FGF18. Hair plucking at high density regenerate hair follicles via TNF‐α. JAG1 + regulatory T lymphocytes regenerate hair follicles. Loss of COL17A1 results in hair follicle miniaturization. Burgundy and navy arrows indicate downregulation and upregulation, respectively. ADRB2, adrenergic receptor B2; BMP2, bone morphogenic protein 2; COL17A1, collagen XVII; DKK1, dickkopf 1; FGF18, fibroblast growth factor 18; FOXP1, forkhead box P1; JAG1, jagged 1; SFRP4, secreted frizzled‐related protein 4; SHH, sonic hedgehog; TNFα, tumour necrosis factor‐α. Re‐pigmentation in Vitiligo. This scheme summarizes recent findings in melanocyte stem cell biology and their implication to re‐pigment vitiligo skin. Melanocyte stem cells reside in lower portion of hair bulge and hair germ at telogen phase and contribute to perifollicular re‐pigmentation. Amplifying melanocytes tend to lose proliferation and migration potential. BMI + CXCR2 + melanocyte stem cells exist in interfollicular epidermis and may contribute to marginal re‐pigmentation. Hair follicle stem cells regulate melanocyte stem cells via cKIT, Wnt and other signals. PAX3 activates MITF, followed by DCT activation, whereas PAX3 directly downregulates DCT and maintains stemness. Noradrenaline induces melanocyte stem cell differentiation and migration via ADRB2. BMI1, B lymphoma Mo‐MLV insertion region 1; cKIT, receptor tyrosine kinase for stem cell factor; CXCR2, chemokine C‐X‐C motif receptor 2; DCT, dopachrome tautomerase; MCAM, melanoma cell adhesion molecule; MITF, microphthalmia associated transcription factor; PAX3, paired box gene 3. Melanocyte Distribution Pattern Differences. The distribution pattern of melanocyte stem cells is different depending on the density of pigmented terminal hair and that of vellus hair. As compared with hair follicle stem cells, melanocyte stem cells are sparsely distributed. Volar melanocyte stem cells reside in eccrine sweat gland and require a long travel to distribute melanocytes in the epidermis. Volar melanocytes is sparse, as compared with melanocytes in hairy skin.